Financial impact of the Safeguards in fruit importing companies in Ecuador - Poveda Burgos, Guido Homero (Revista Universidad de Guayaquil, 2016)
The safeguards in the Ecuador wereimplemented from March 11, 2 015 and his duration is 15 months, the Government established tnis measure to be able to obtain economic resources and offer protection to the local producers wno meet affected by tne products from the exterior, concerning directly to the importing and consuming ends. One of the principal sectors seriously affected by the safeguards corresponds to the importers of Fruits, which were commercializing foreign fruits to be able to supply the local market in the whole Ecuador, with the safeguards these companies reduced his imports, doing that the final consumer acquires the national product. The percentage implemented for the imported fruit was 45 P by which his costs were raised, the earnings of the companies diminished and the final consumer acquired less this product, but the Government compromised itself with the World Organization of Trade "WTO" in the reduction of this tax, so in January, 2 016 the reduction was approved to 40 P.
Keywords: importers; final consumer; World Organization of Trade; tax